George and Pat Kamp's 25th Anniversary Reno Moose Lodge - Watkins, Howard::::::::: (1989)
Christine Watkins, Adam Watkins, George Kamp, Robin Watkins, Patricia Kamp and Sherry Butolph and 2-tiered wedding anniversary cake